2019
DOI: 10.1101/696385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beta-driven closed-loop deep brain stimulation can compromise human motor behavior in Parkinson’s Disease

Abstract: Closed-loop or adaptive deep brain stimulation (DBS) for Parkinson's Disease (PD) has shown comparable clinical improvements to continuous stimulation, yet with less stimulation times and side effects. In this form of control, stimulation is driven by pathological beta oscillations recorded from the subthalamic nucleus, which have been shown to correlate with PD motor symptoms. An important consideration is that beta activity is itself modulated during volitional movements, yet it is unknown the impact that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…3). Of relevance, the use of a suboptimal biomarker could be detrimental, possibly interfering with the FM needed for the transition from upright quiet standing to steady state walking [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Of relevance, the use of a suboptimal biomarker could be detrimental, possibly interfering with the FM needed for the transition from upright quiet standing to steady state walking [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, caution is warranted in using beta oscillations for aDBS, as they are relevant for many perceptual, cognitive, and motor physiological processes [14]. Indeed, while ameliorating certain symptoms, power beta modulation might impair the residual task-related physiological coding capacity of the stimulated area [15]. Furthermore, amplitude modulation might not capture circuit dynamics, such as frequency-and phase-specific synchronization [16,17], which would be fundamental in routing the information flow across distant brain areas [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, this might reflect the reduction in the response of bradykinesia items to stimulation reported in some of the studies following DBS patients for more than 5 years [ 3 , 4 ]. This may also explain why the level of improvement in subUPDRS scores with both aDBS and cDBS (~20%) was at the lower limit of the range of improvements seen under similar blinded conditions when these interventions are contrasted acutely following electrode implantation [ 9 , 10 , 12 , 14 , 32 ]. Note too that scores from blinded video assessments are lower than those made during direct, unblinded clinical examination [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this might reflect the reduction in the response of bradykinesia items to stimulation reported in some of the studies following DBS patients for more than 5 years [3,4]. This may also explain why the level of improvement in subUPDRS scores with both aDBS and cDBS (~20%) was at the lower limit of the range of improvements seen under similar blinded conditions when these interventions are contrasted acutely following electrode implantation [9,10,12,14,33]. Note too that scores from blinded video assessments are lower than those made during direct, unblinded clinical examination [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have confirmed the efficacy of 'beta-based' aDBS [9][10][11][12][13], and suggested a superior side effect profile compared to continuous, conventional, DBS (cDBS) [14,15], these have been mostly performed in newly implanted patients. Such studies are potentially compromised by the microlesion effect [16], as this confounding factor provides temporary symptom relief, which can mask the true effects of stimulation.…”
Section: Introductionmentioning
confidence: 99%